Steps in the construction and verification of an explanatory model of psychosocial adjustment - Rodríguez-Fernández, Arantzazu; Ramos-Díaz, Estibaliz; Madariaga, José María; Arrivillaga, Ana; Galende, Nuria (European journal of education and psychology, 2016)
The aim of the present study was to empirically test an explanatory model of psychosocial adjustment during adolescence, with psychosocial adjustment during this stage being understood as a combination of school adjustment (or school engagement) and subjective well-being. According to the hypothetic model, psychosocial adjustment depends on self-concept and resilience, which in turn act as mediators of the influence of perceived social support (from family, peers and teachers) on this adjustment. Participants were 1250 secondary school students (638 girls and 612 boys) aged between 12 and 15 years (Mean=13.72; SD=1.09). The results provided evidence of: (a) the influence of all three types of perceived support on subject resilience and self-concept, with perceived family support being particularly important in this respect; (b) the influence of the support received from teachers on school adjustment and support received from the family on psychological wellbeing; and (c) the absence of any direct influence of peer support on psychosocial adjustment, although indirect influence was observed through the psychological variables studied. These results are discussed from an educational perspective and in terms of future research. El presente trabajo tiene como objetivo someter a comprobación empírica un modelo explicativo sobre el ajuste psicosocial en la adolescencia, entendiendo el ajuste psicosocial en este etapa de la vida como la conjunción del ajuste escolar (o implicación en la escuela) y el bienestar subjetivo. Según este modelo hipotetizado, el ajuste psicosocial depende del autoconcepto y de la resiliencia, que a su vez funcionan como mediadores de la influencia del apoyo social percibido (de la familia, pares y profesorado) sobre dicho ajuste. Participaron en esta investigación un total de 1250 estudiantes de ESO (638 mujeres y 612 hombres) de entre 12 y 15 años (M=13.72; DT=1.09). Los resultados aportan evidencias de: a) la influencia de los tres tipos de apoyo percibido sobre la capacidad de resiliencia y sobre el nivel de autoconcepto, destacando el de la familia; b) del apoyo del profesorado sobre el ajuste escolar y de la familia sobre el bienestar psicológico; y c) del nulo influjo directo del apoyo de los amigos sobre el ajuste psicosocial, pero sí indirecto a través de las variables psicológicas. Estos datos se discuten tanto desde perspectivas educativas como en orden a futuras investigaciones.